2016
DOI: 10.1091/mbc.e15-02-0101
|View full text |Cite
|
Sign up to set email alerts
|

Augmin shapes the anaphase spindle for efficient cytokinetic furrow ingression and abscission

Abstract: Perturbations of the central spindle by depletion of a microtubule nucleation regulator, augmin, revealed its unexpected contributions to the control of cleavage furrow ingression, as well as to cytokinesis completion. These are achieved through nonredundant targeting mechanisms of cytokinesis regulators.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 82 publications
(125 reference statements)
0
33
0
Order By: Relevance
“…Rat anti‐α‐tubulin (YOL1/34, EMD Millipore, Temecula, CA; 1 : 500 for IB), rat anti‐GFP (GF090R, Nacalai, Kyoto, Japan; 1: 1000 for IB), goat antianillin (sc‐54859, Santa Cruz Biotechnology, Dallas, TX; 1 : 500 for IF), rabbit antianillin (A301‐405A, Bethyl Laboratories, Montgomery, TX; 1 : 50 for IB), mouse antiezrin (sc‐58758, Santa Cruz Biotechnology; 1 : 100 for IF and 1 : 100 for IB), rabbit antiradixin (EP1862Y, GeneTex, Irvine, CA; 1 : 200 for IF and 1 : 10 000 for IB), rabbit antimoesin (3150, Cell Signaling Technology, Danvers, MA; 1 : 300 for IF and 1 : 1000 for IB), rabbit antisupervillin (NBP1‐90363, Novus Biotechnologicals, Littleton, CO; 1 : 200 for IF and 1 : 500 for IB), mouse anti‐RhoA (sc‐418, Santa Cruz Biotechnology; 1 : 100 for IF), rabbit anti‐RhoA, B, C (EPR18299, Abcam Cambridge, United Kingdom; 1: 500 for IF), rabbit antimyosin IIA (a gift from Dr. K. Owaribe; 1 : 1000 for IF) , mouse anti‐MLKP1 (a gift from Dr. K. Yoda; 1 : 2 for IF) , and fluorescence‐ or horseradish peroxidase‐conjugated secondary antibodies (Jackson ImmunoResearch Laboratories, West Grove, PA; 1 : 1000 for IF and IB) were purchased from the suppliers and used at the dilutions as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…Rat anti‐α‐tubulin (YOL1/34, EMD Millipore, Temecula, CA; 1 : 500 for IB), rat anti‐GFP (GF090R, Nacalai, Kyoto, Japan; 1: 1000 for IB), goat antianillin (sc‐54859, Santa Cruz Biotechnology, Dallas, TX; 1 : 500 for IF), rabbit antianillin (A301‐405A, Bethyl Laboratories, Montgomery, TX; 1 : 50 for IB), mouse antiezrin (sc‐58758, Santa Cruz Biotechnology; 1 : 100 for IF and 1 : 100 for IB), rabbit antiradixin (EP1862Y, GeneTex, Irvine, CA; 1 : 200 for IF and 1 : 10 000 for IB), rabbit antimoesin (3150, Cell Signaling Technology, Danvers, MA; 1 : 300 for IF and 1 : 1000 for IB), rabbit antisupervillin (NBP1‐90363, Novus Biotechnologicals, Littleton, CO; 1 : 200 for IF and 1 : 500 for IB), mouse anti‐RhoA (sc‐418, Santa Cruz Biotechnology; 1 : 100 for IF), rabbit anti‐RhoA, B, C (EPR18299, Abcam Cambridge, United Kingdom; 1: 500 for IF), rabbit antimyosin IIA (a gift from Dr. K. Owaribe; 1 : 1000 for IF) , mouse anti‐MLKP1 (a gift from Dr. K. Yoda; 1 : 2 for IF) , and fluorescence‐ or horseradish peroxidase‐conjugated secondary antibodies (Jackson ImmunoResearch Laboratories, West Grove, PA; 1 : 1000 for IF and IB) were purchased from the suppliers and used at the dilutions as indicated.…”
Section: Methodsmentioning
confidence: 99%
“…The bidirectional cortical flow towards the cell equator contributes to the equatorial accumulation of the actomyosin network and to the cleavage furrow formation (DeBiasio et al, 1996;Reymann et al, 2016;Salbreux et al, 2009;Turlier et al, 2014;Werner et al, 2007;Zhou and Wang, 2008). In addition to the central spindle, the molecules for equatorial simulation can be recruited to the anti-parallel overlaps of the equatorial astral microtubules (Argiros et al, 2012;D'Avino et al, 2006;Nguyen et al, 2014;Nishimura and Yonemura, 2006;Su et al, 2014;Uehara et al, 2016) and to the microtubule ends that laterally associate with the furrow cortex in monopolar cytokinesis (Canman et al, 2003;Hu et al, 2008;Kitagawa et al, 2013;Shrestha et al, 2012). It has also been reported that precise microtubule polymerization/depolymerization dynamics does not play a crucial role for furrow induction (Strickland et al, 2005).…”
Section: Materials and Methods Andmentioning
confidence: 99%
“…Previously, we had found that depletion of a spindle-associated protein complex, augmin, suppressed MT generation within the mitotic spindle and instead enhanced development of prominent astral MTs during anaphase in HeLa cells (Uehara et al, 2016). Therefore, we tested the effect of augmin depletion on the progression of centriole disengagement and subsequent centriole duplication in haploid HAP1 cells.…”
Section: Ploidy-dependent Difference In Astral Mt Development Determimentioning
confidence: 96%